2007
DOI: 10.1007/s00414-007-0199-x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of metric sex analysis of skeletal remains using Fordisc® based on a recent skull collection

Abstract: It has been generally accepted in skeletal sex determination that the use of metric methods is limited due to the population dependence of the multivariate algorithms. The aim of the study was to verify the applicability of software-based sex estimations outside the reference population group for which discriminant equations have been developed. We examined 98 skulls from recent forensic cases of known age, sex, and Caucasian ancestry from cranium collections in Frankfurt and Mainz (Germany) to determine the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 32 publications
1
16
0
2
Order By: Relevance
“…Another caveat must be to use discriminant functions only on cases that are known to come from the same population from which the functions were derived [11,23,32], except for a population with similar mean values of the variables and expression of sexual dimorphism in the foramen magnum area. Particularly, in forensic cases, only methods developed on documented skeletal samples of known age, sex and ethnicity should be used.…”
Section: Discussionmentioning
confidence: 99%
“…Another caveat must be to use discriminant functions only on cases that are known to come from the same population from which the functions were derived [11,23,32], except for a population with similar mean values of the variables and expression of sexual dimorphism in the foramen magnum area. Particularly, in forensic cases, only methods developed on documented skeletal samples of known age, sex and ethnicity should be used.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological trait analyses for sexing skeletons are well established, but they may be difficult due to breakage or postmortem damage of the skeletal remains. Ramsthaler et al [29] verified the applicability of software-based sex estimations outside the reference population group for which discriminant equations were developed. Braga and Treil [30] developed a method for estimating the skeletal age of children based on the centroid size of their face and their basicranium, derived from the three-dimensional coordinates of anatomical landmarks and showed that the centroid size of the facial skeleton can be used an age-related variable without any loss of accuracy with increased age, contrary to most of the methods of pediatric age estimation.…”
Section: Discussionmentioning
confidence: 98%
“…An anthropometric investigation comparing cranial and postcranial elements for sex estimation revealed that postcranial skeleton performs better than cranial when using multivariate analysis [36]. Skull measurements were applied on a validation study conducted by Ramsthaler et al [37]. The authors tested USA discriminant functions on a German sample to compare the use of Fordisc data versus morphological assessment.…”
Section: Discussionmentioning
confidence: 99%